KONSEP DIRI MAHASISWA BIDIKMISI DI UNIVERSITAS JEMBER - Garniasih, Belly; Jannah, Raudlatul (Jurnal ENTITAS SOSIOLOGI, 2018)
One of the scholarship programs in the University of Jember which annually provide plenty of quotas is a scholarship through Bidikmisi program given to students who came from an economically poor family and good achievement history. As known that ideally, Bidikmisi students must behave, appear and act in accordance with Bidikmisi scholarship?s definition itself in order to prevent misunderstanding in the use of scholarship?s fund. But still, there are several Bidikmisi students in the University of Jember who doesn?t display the ?ideal? definition. From this phenomenon then lead to a question about ?Self-concept of Bidikmisi Students at the University of Jember?. In this study, the researcher uses qualitative descriptive approve, which aims to get information about the self-concept of Bidikmisi students at the University of Jember. The theory used is symbolic interactionism by George Herbert Mead, which the theory explained that someone is seen as an actor which interpret, judge, define, act and explain about the use of symbols as a form of interpretation in someone interaction with another or with a group. The symbols used cold to be in verbal form or nonverbal.  The result of the study shows that there are two kinds of self-concept of Bidikmisi students, namely positive concept and negative concept. Positive self-concept namely (1) make the parents proud (2) get a high achievement and aspirations (3) responsible. On the other hand, negative self-concept is (1) feeling inferior (2) overconfidence.     Keywords: self-concept, Bidikmisi students